Chemical attributes of a Hapludox soil after nine years of pig slurry application - Veiga, Milton da (2013)
The objective of this study was to evaluate the pig slurry application effects on chemical attributes of a Hapludox soil managed under no‑tillage system. Treatments consisted of 50, 100 and 200 m3 ha-1 per year of pig slurry application, and a control with replacement of P and K exported through harvested grains. Attributes related to soil chemical reaction, exchange complex, and nutrient contents were determined in soil samples collected in the ninth year of experimentation from 0–0.025, 0.025–0.05, 0.05–0.10, 0.10–0.20, 0.20–0.40 and 0.40–0.60 m soil depths. The continuous application of high doses of pig slurry on the Oxisol surface under no‑tillage acidifies the soil and increases Al, P, Cu, and Zn contents down to 0.2‑m depth, and K levels down to 0.6‑m depth.